2018
DOI: 10.1002/glia.23482
|View full text |Cite
|
Sign up to set email alerts
|

Parkin targets NOD2 to regulate astrocyte endoplasmic reticulum stress and inflammation

Abstract: Loss of substantia nigra dopaminergic neurons results in Parkinson disease (PD). Degenerative PD usually presents in the seventh decade whereas genetic disorders, including mutations in PARK2, predispose to early-onset PD. PARK2 encodes the parkin E3 ubiquitin ligase which confers pleotropic effects on mitochondrial and cellular fidelity and as a mediator of endoplasmic reticulum (ER) stress signaling. Although the majority of studies investigating ameliorative effects of parkin focus on dopaminergic neurons w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 66 publications
(90 reference statements)
1
38
0
Order By: Relevance
“…PINK1 has a low basal expression which is undetectable with immunohistochemical methods, and its finding in spheroids suggests it accumulates in their mitochondria. Parkin normally exists in an inactive auto‐inhibited conformation which changes when its serine 65 is phosphorylated by the action of the autophosphorylated PINK1 (Chin & Li, 2016; Pickrell & Youle, 2015; Singh et al, 2018). The spheroids showed high parkin immunoreactivity, a fact also found for ubiquitin, a protein which links covalently to other proteins (ubiquitination) and works as a “kiss of death” signal for mitophagy (Chin & Li, 2016; de Rivero Vaccari et al, 2012; Rogov, Dotsch, Johansen, & Kirkin, 2014; C. Y. Wang, Deneen, & Tzeng, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…PINK1 has a low basal expression which is undetectable with immunohistochemical methods, and its finding in spheroids suggests it accumulates in their mitochondria. Parkin normally exists in an inactive auto‐inhibited conformation which changes when its serine 65 is phosphorylated by the action of the autophosphorylated PINK1 (Chin & Li, 2016; Pickrell & Youle, 2015; Singh et al, 2018). The spheroids showed high parkin immunoreactivity, a fact also found for ubiquitin, a protein which links covalently to other proteins (ubiquitination) and works as a “kiss of death” signal for mitophagy (Chin & Li, 2016; de Rivero Vaccari et al, 2012; Rogov, Dotsch, Johansen, & Kirkin, 2014; C. Y. Wang, Deneen, & Tzeng, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous report, MK exhibited inhibitory effects on LPS-induced nitric oxide production in RAW 264.7 macrophages [ 30 ] and inhibited 5-lipoxygenase and OVA-induced airway inflammation [ 67 ]. Moreover, Singh et al showed that parkin can target the nucleotide binding oligomerization domain containing 2 protein (NOD2) to regulate astrocyte endoplasmic reticulum stress and inflammation [ 68 ]. In our study, MK could increase parkin expression and may reverse astrocyte-associated inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…SH3GL2 is also responsible for recruitment of dynamin to clathrin-coated vesicles (20). Parkin interacts with NOD2 for regulation of stress and inflammation; Parkin knockdown in mouse dopaminergic neurons exhibited increased NOD2 expression and endoplasmic reticulum stress and cytokine release (21). NOD2 deficiency was protective against 6-OHDA-induced DA degeneration and neuronal death (22), suggesting that the identified NOD2 variants in our patients may be toxic gain of function.…”
Section: Discussionmentioning
confidence: 83%